Monsenhor Soares e a educação em Propriá (1949-960) - Freitas, Simone Silvestre Santos (2014)
This study aims to analyze the trajectory of Monsignor José Soares Curvelo in the city of Propriá - SE, in the period from 1949 to 1960, emphasizing their educational practices in this city, presenting their works, their commitment and coping conflict in search of the extension offer schooling for the local population. The sources were located inside the books of Acts of Union Benevolent Society Propriá (SUB), the books of the Diocese of Aracaju Tombo and Propriá 1949 to 1960, the newspaper "The Defense" Propriá, between the years 1950 to 1960, and records in the Historical and Geographical Institute of Sergipe. The theoretical and methodological procedures adopted are linked to the assumptions of Cultural History and Biographical Approach. The main categories of analysis are mobilized: civilization Norbert Elias (1994), Social Capital, Cultural Capital and Educational System of Bourdieu (1998), strategy the Michel the Certeau; Document / Monument Le Goff (1998) and intellectual Sirinelli (2003). Monsignor José Soares Curvelo had a key role in education Propriá, with the intention of such research, study that historic moment, trying to understand how built up this character and his works, and realize the contributions to the history of education in Sergipe.